The Screen-scape of Advertising: Trends and Innovation - Muzaffar, Naima; Khattak, Mehrbano; Yousafzai, Rabeea (Journal of Peace, Development and Communication, 2024)
The field of advertising has undergone a rapid transformation, power-sourced by technological advancements and changes in viewpoint, that has contributed towards consumer’s behavior, resulting in an ever-evolving market. This paper attempts to explore the trends and innovations that have played a part in shaping the current face and future of the screen-scape of advertising, which includes the rise of digital platforms, personalized content, and integration of emerging technologies. This paper delves into the idea of how by embracing these new trends and enriching ethical practices, advertisers can forge deeper connections with consumers, thereby navigating the complexities of an ever-changing techno-environment. The discourse also examines the challenges and opportunities that are presented by these trends and offers insights into how advertisers can adapt and thrive in this dynamic environment. Key Words: advertising, transformation, trends, innovations, consumer, mixed reality, extended reality